Temporary mesenteric venous shunting for portal vein reconstruction: A novel technical adjunct - Jon G. Quatromoni, MD; Robert Roses, MD; Major K. Lee, MD, PhD; Oksana A. Jackson, MD; Benjamin M. Jackson, MD; Ann C. Gaffey, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
Pancreatic resection not infrequently requires portal vein (PV) repair or replacement. PV reconstruction often requires bypass grafting or patch venoplasty, and these grafts and patches require time to thaw or harvest. Mesenteric ischemia and congestion with associated bowel edema may result from prolonged venous occlusion during thawing, harvesting, and reconstructing. Temporary shunting of the mesenteric venous circulation may mitigate these adverse effects. Twenty-one patients were shunted using Argyle shunts during PV reconstruction from 2010 to 2020. Reconstructions in this series consisted of aortic homograft interposition grafts (52%), bovine pericardial patches (38%), internal jugular vein interposition grafts (5%), and internal jugular patches (5%). No intraoperative complications resulted from shunt placement; technical success of PV reconstruction was 100%. Temporary venous shunting during PV reconstruction is safe, technically straightforward, and may serve to decrease the duration of venous mesenteric occlusion.